Pokemon Detective Pikachu - Letterman, Rob; Hernandez, Dan 1983-; Samit, Benji 1984-; Perlman, Nicole; Connolly, Derek; Parent, Mary; Boyter, Cale 1972-; Katakami, Hidenaga; McGowan, Don (Producer); Reynolds, Ryan; Smith, Justice 1995-; Newton, Kathryn 1997-; et al. (Burbank, CA : Warner Bros. Home Entertainment, 2019)
The story begins when ace private eye Harry Goodman goes mysteriously missing, prompting his 21-year-old son Tim to find out what happened. Aiding in the investigation is Harry's former Pokemon partner, Detective Pikachu: a hilariously wisecracking, adorable super-sleuth who is a puzzlement even to himself. Finding that they are uniquely equipped to communicate with one another, Tim and Pikachu join forces on a thrilling adventure to unravel the tangled mystery.
Based on the "Detective Pikachu" video game.
Originally released as a motion picture in 2019.
Wide screen.
Bonus disc: special features : Alternate opening ; My Pokemon adventure ; Creating the world of Detective Pikachu featurettes ; Mr. Mime's audio commentary ; Ryan Reynolds: outside the actor's studio ; "Carry on" music video by Rita Ora & Kygo.
Director of photography, John Mathieson ; editors, Mark Sanger, James Thomas ; music, Henry Jackman.
Ryan Reynolds, Justice Smith, Kathryn Newton, Suki Waterhouse, Omar Chaparro, Chris Geere, Rita Ora, Karan Soni, Josette Simon, Ken Watanabe, Bill Nighy.
Keywords: Pikachu -- (Fictitious character) -- Juvenile films; Pokemon (Fictitious characters) -- Juvenile films; Film adaptations; DVD-Video discs; Action and adventure films; Children's films; Comedy films; Feature films; Fiction films; Juvenile works; Video recordings for people with visual disabilities; Video recordings for the hearing impaired